Effects of Plastic Storage Containers and Time on Potable Water (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Water tanks are liquid storage containers that store water for human consumption. They are usually made of polyethylene (plastic), steel, clay, ceramics and fiber glass. The need to investigate the changes in water quality during storage in different types of water storage tanks or vessels is very crucial in establishing which tank contributes to deterioration or improvement of stored water during storage. Two sources of potable water (tap water and borehole water) were stored in three water storage tanks for a period of six weeks. The tanks include black plastic tank, blue plastic tank and green plastic tank. The water quality parameters examined were Temperature, Taste, Odour, Colour, Turbidity, Conductivity, pH and Total Heterotrophic Bacteria (THB). However, all parameters listed above were analyzed at a sampling frequency of seven days interval. The results showed that among the different coloured storage tanks used, black plastic tank was the best in terms of preserving water quality. The range in the following examined toxic parameters Total heterotrophic bacteria in tap water stored in black plastic tank, green plastic tank and blue plastic tank were 2×102CFU/100mL – 106×102CFU/100mL, 2×102CFU/100mL – 116×102CFU/100mL and 2×102CFU/100mL – 118×102CFU/100mL respectively. On the other hand, the range for the said parameters for borehole water stored in black plastic tank, green plastic tank and blue plastic tank were respectively 6×102CFU/100mL – 100×102CFU/100mL, 6×102CFU/100mL – 104×102CFU/100mL and 6×102CFU/100mL – 108×102CFU/100mL. Also, findings from the study recommends that, the maximum retention period for storing tap water or borehole water in plastic tanks to be at most 3weeks. From this work, it was established that, black plastic materials should be considered first when selecting a container material for storing water in large capacity.